Classroom engagement dynamics: examining the potency of reflective teaching approach among some selected universities in Ghana. Issue 6 (2nd November 2017) - Salifu, Inusah; Worlanyo, Emile Kwadwo; Kuyini, Ahmed Bawa
Abstract: The purpose of this research was to investigate the effectiveness of the use of reflective teaching approach by university lecturers in Ghana to achieve improved student learning outcomes. The research utilised a quantitative survey design involving 180 lecturers who were accidentally or haphazardly selected from four universities in Ghana to complete a reflective teaching survey (RTS) questionnaire. The results showed that participants frequently engaged in varied reflective teaching activities, and were successful in evaluating the effectiveness of their pedagogies. The research concluded that the approach should be an essential component of the teacher performance appraisal system.